Development of Design Thinking-Based Challenge Cards to Improve Discipline and Critical Thinking of Junior High School Grade 7h Students in Social Studies Learning (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The lack of discipline among junior high school students in social studies learning affects the effectiveness of the educational process. Initial observations in Class 7H at SMP Lab Lab, State University of Malang, revealed that students often ignored class rules, failed to follow teacher instructions, submitted assignments late, and were inactive in group work. To address these issues, Challenge Cards were developed as a learning medium based on Design Thinking to foster discipline through structured and engaging learning tasks. This study used a Research and Development (R&D) strategy with a qualitative descriptive method. The development process followed five stages of Design Thinking. In the Empathize stage, observations and interviews were conducted to identify the causes of low discipline, such as procrastination and lack of responsibility. The Define stage formulated the core problem as the absence of a learning strategy that includes time limits and clear task structures. During the Ideate stage, Challenge Cards were designed with social case studies to be completed sequentially within a time frame. A prototype consisting of five challenge levels and group task scenarios was tested in the Test stage. The results showed improved discipline, including punctual submissions, teamwork, and rule compliance. The media proved effective, engaging, contextual, and encouraged active student responsibility.